1995
DOI: 10.1002/jbt.2570100502
|View full text |Cite
|
Sign up to set email alerts
|

Altered glycine transport by cerebral tissue and decreased Na+ and Ca++ pump activities during organophosphorus‐ester–induced delayed neurotoxicity development period

Abstract: Uptake of [U-14C] glycine during the organophosphorus-ester-induced delayed neurotoxicity (OPIDN) development period was studied. Diisopropyl fluorophosphate (DFP), a delayed neurotoxic organophosphorus ester was administered to adult rats and hens. Results showed a decreased accumulation of glycine in hen cerebral cortex slices during the delayed neurotoxicity development period. An altered sensitivity toward transport inhibitors 2,4-dinitrophenol and ouabain was observed in DFP-treated hens. An altered neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The steps from NTE inhibition to development of neuropathy are not clear. In addition to NTE inhibition, cytoskeleton abnormalities (Abou-Donia 1995), altered membrane function (Sharma and Bhattacharya 1995), induction of c-jun (Damodaran et al 2000), alterations in dopaminergic system (Choudhary et al 2002), aberrant activation of CDK5 (Wang et al 2006), activation of MAP Kinase (Hargreaves et al 2006), and CREB (Damodaran et al 2002) have been observed in experimental models of OPIDN.…”
Section: Introductionmentioning
confidence: 98%
“…The steps from NTE inhibition to development of neuropathy are not clear. In addition to NTE inhibition, cytoskeleton abnormalities (Abou-Donia 1995), altered membrane function (Sharma and Bhattacharya 1995), induction of c-jun (Damodaran et al 2000), alterations in dopaminergic system (Choudhary et al 2002), aberrant activation of CDK5 (Wang et al 2006), activation of MAP Kinase (Hargreaves et al 2006), and CREB (Damodaran et al 2002) have been observed in experimental models of OPIDN.…”
Section: Introductionmentioning
confidence: 98%
“…11 However, NTE activity returns to normal well before the onset of clinical and morphological signs, 11 suggesting that the precise biochemical mechanism involved in the development of OPIDN is not well understood. Besides, studies done with experimental model of OPIDN have shown cytoskeleton abnormalities, 12 alterations in dopaminergic system, 13,14 altered membrane function, 15 aberrant activation of cyclin-dependent kinase 5 (CDK5), 16 activation of mitogen-activated protein (MAP) kinase 17 and cAMP-response element binding (CREB), 18 induction of c-jun, 19 decreased ATP production, impaired mitochondrial functions 20 and mitochondrial integrity. 21 Oxidative stress has long been linked to the neuronal cell death that is associated with many neurodegenerative conditions.…”
Section: Introductionmentioning
confidence: 99%